Given:
The first term of the sequence is

The nth term of the sequence is

We need to determine the 7th term of the sequence.
Second term:
Substituting n = 2 in the nth term of the sequence, we get;




Thus, the second term of the sequence is 32.
Third term:
Substituting n = 3 in the nth term of the sequence, we get;



Thus, the third term of the sequence is 16.
Fourth term:
Substituting n = 4 in the nth term of the sequence, we get;



Thus, the fourth term of the sequence is 8.
Fifth term:
Substituting n = 5 in the nth term of the sequence, we get;



Thus, the fifth term of the sequence is 4.
Sixth term:
Substituting n = 6 in the nth term of the sequence, we get;



Thus, the sixth term of the sequence is 2.
Seventh term:
Substituting n = 7 in the nth term of the sequence, we get;



Thus, the seventh term of the sequence is 1.